ANALISIS ARGUMENTASI HUKUM DAN RATIO DECIDENDI DALAM SENGKETA PPN DI PENGADILAN PAJAK PADA PUTUSAN PENGADILAN PAJAK NOMOR : PUT-005266.16/2023/PP/M.XIB - Olina Rizki Arizal; Rizky Karo Karo (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
The resolution of tax disputes in court is not without its challenges, one of which is the complexity of formulating legal arguments. This study aims to analyze the Tax Court Judge's Decision on the VAT dispute involving PT. Cipta Dwi Busana and examine strong legal arguments in the VAT dispute at the Tax Court of PT. Cipta Dwi Busana. The method used in this research is normative juridical. This study analyzes Decision No. PUT-005266.16/2023/PP/M.XIB of 2024, with legal sources drawn from laws related to taxation and Value Added Tax (VAT). The analysis technique involves linking primary legal sources with supporting theories and literature, including books and journals, and is presented descriptively. The results of this study indicate that Decision No. PUT-005266.16/2023/PP/M.XIB of 2024 fully granted PT. Cipta Dwi Busana's appeal against the Director General's Decision, based on taxation laws and legal arguments. The arguments referenced include PMK 32/PMK.010/2019, Law of the Republic of Indonesia Number 42 of 2009, Articles 1 Paragraphs 17 and 19, and Government Regulation of the Republic of Indonesia Number 1 of 2012.